2021
DOI: 10.1002/ar.24626
|View full text |Cite
|
Sign up to set email alerts
|

Sexual differences in human cranial morphology: Is one sex more variable or one region more dimorphic?

Abstract: The quantification of cranial sexual dimorphism (CSD) among modern humans is relevant in evolutionary studies of morphological variation and in a forensic context. Despite the abundance of quantitative studies of CSD, few have specifically examined intra-sex variability. Here we quantify CSD in a geographically homogeneous sample of adult crania, which includes Italian individuals from the 19th and 20th centuries. Cranial morphology is described with 92 3D landmarks analyzed using Procrustean geometric morphom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 95 publications
(130 reference statements)
5
33
4
Order By: Relevance
“…Gender differences of size were established well before puberty and our study suggests that males experienced subtly different patterns of brain and of cranial aging as well as growth. These findings are consistent with recent work published by Smith et al (2020;Smith, Duncan, Pears, Profico & O'Higgins, 2021) as well as Milella et al (2021). We find no evidence that the aged adult cranium is more variable due to, for example, fragility nor that covariations were any weaker or stronger compared with middle aged adults.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Gender differences of size were established well before puberty and our study suggests that males experienced subtly different patterns of brain and of cranial aging as well as growth. These findings are consistent with recent work published by Smith et al (2020;Smith, Duncan, Pears, Profico & O'Higgins, 2021) as well as Milella et al (2021). We find no evidence that the aged adult cranium is more variable due to, for example, fragility nor that covariations were any weaker or stronger compared with middle aged adults.…”
Section: Discussionsupporting
confidence: 93%
“…More recently, Smith et al's (2020) analyses of surface landmarks has suggested that craniofacial sexual dimorphism is mostly size related and that males follow an extended growth trajectory (hypermorphosis). This size offset has also been confirmed in a recent study of skeletal landmarks (Milella, Franklin, Belcastro, & Cardini, 2021) with males, on average, more prognathic and dolichocephalic compared with females. In the present study, we test for sexual dimorphism in the size and shape of the brain as well as of the cranium across a large population, including during ontogeny and adulthood.…”
Section: Adulthoodsupporting
confidence: 68%
“…This finding support previous studies that found that cranial morphology is largely influenced by size, with males having larger cranial size (Franklin et al, 2006;Gonzalez et al, 2011;Green & Curvoe, 2009;Kimmerle et al, 2008;Rosas & Bastir, 2002). This has also been observed in earlier studies analyzing the occipital (Chovalopoulou et al, 2013;Guyomarc'h & Bruzek, 2010) and the temporal bones (Guyomarc'h & Bruzek, 2010;Milella et al, 2021), as it has also been seen in other skeletal regions (Bastir et al, 2014;García-Martínez et al, 2016). On the regression graph (Figure 8), it appears that the size range of females is substantially comprised into the size range of males, suggesting that the highly significant differences could in fact be driven by a handful of particularly large males.…”
Section: Size and Shape Differences On Occipital And Temporal Bonessupporting
confidence: 92%
“…Nevertheless, those two specific PCs only represent 22.74% of the overall variation. Previous authors noted intraspecific variations on either both temporal bones (Guyomarc'h & Bruzek, 2010) or on the left one (Milella et al, 2021). Franklin also observed in a South‐African sample, a larger mastoid process in length and height, in males, with considerable antero‐inferior projection (Franklin et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation